POLITYCZNA POPRAWNOŚĆ DYSKURSU EDUKACYJNEGO: NAUCZYCIEL JĘZYKA OBCEGO W PRZECIWDZIAŁANIU MOWIE NIENAWIŚCI - Lankiewicz, Hadrian; Szczepaniak-Kozak, Anna (Neofilolog, 2018)
This paper presents an attempt to reconsider the concept of intercultural communication and related competences taking into account the fact that intercultural contacts may be motivated by racism and xenophobia. It is the outgrowth of the RADAR project (Regulating Anti-Discrimination and Anti-Racism) funded by the European Commission1. Here, we aim to apply its findings to the context of developing politically correct pedagogical discourse among prospective foreign language teachers. Ultimately, invoking the notion of critical ecological language awareness (Lankiewicz, 2015) and metalinguistic awareness (Karpińska-Musiał, 2015), we offer to supplement the intercultural component of teacher education with the element of critical linguistics, which may help would-be teachers, in the first place, to be more aware language users as such, not to commit verbal offences, and, in the long-run, to perform the role of transformative intellectuals (Kumaravadivelu, 2012), thus contributing to the quality of life in the globalization era.